BRAZIL IN THE FACE OF THE NEOLIBERAL OFFENSIVE: notes of a tragedy announced - Miranda, Gabriel; Lemos de Paiva, Ilana (Universidade de Brasília, 2021)
This exploratory paper intends to present a debate about neoliberalism, demarcating some of its general characteristics and, in addition, to analyze the political context in which such an economic program is intensified in Brazil from 2016, outlining some of the implications of this process for the labor class. Keywords: neoliberalism; conservatism; necropolitics.